MENGUNGKAP FAKTA FAKTOR RISIKO DIABETES MELITUS DI INDONESIA - Azriful Azriful; Yudi Adnan; Emmi Bujawati; Syamsul Alam; Nildawati Nildawati (Poltekkes Kemenkes Bandung, 2024)
The increase in the prevalence of diabetes mellitus in Indonesia is influenced by the interaction of internal and external multifactors. The incidence of DM is predicted to continue to increase to reach 578 million in 2030 and 700 million in 2045. This study aimed to analyze factors related to the incidence of diabetes in Indonesia. This research used quantitative methods with a cross sectional approach and uses secondary data taken from the source